2020
DOI: 10.1111/joa.13203
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of tight junctions contributes to hyposalivation of salivary glands in a mouse model of type 2 diabetes

Abstract: Tight junction (TJ) plays an important role in regulating paracellular fluid transport in salivary glands; however, little is known about the involvement of TJs in diabetes salivary glands. This study aimed to investigate the alterations of TJs and their possible contribution in diabetes‐induced hyposalivation. Here, we observed that the morphologies of submandibular glands (SMGs) were impaired, characterized by enlarged acini accumulation with giant secretory granules, which were significantly reduced in atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
(69 reference statements)
2
17
0
Order By: Relevance
“…In keeping with our earlier statement, that barrier leak in diabetes is systemic and across many tissue types, diabetes-associated hyposalivation was shown to associate with altered TJ protein expression in parotid glands [ 23 ]. In addition, gestational diabetes in a rat model induced increased leak across the placental barrier along with decreased ZO-1 and occludin expression [ 238 ].…”
Section: Is Epithelial Barrier Compromise a Common Occurrence In Dise...supporting
confidence: 87%
See 1 more Smart Citation
“…In keeping with our earlier statement, that barrier leak in diabetes is systemic and across many tissue types, diabetes-associated hyposalivation was shown to associate with altered TJ protein expression in parotid glands [ 23 ]. In addition, gestational diabetes in a rat model induced increased leak across the placental barrier along with decreased ZO-1 and occludin expression [ 238 ].…”
Section: Is Epithelial Barrier Compromise a Common Occurrence In Dise...supporting
confidence: 87%
“…Animal studies have shown that the association holds for much more than simply the intestinal barrier. Huang and Gu [ 23 , 24 ] offer examples of blood–brain barrier (BBB) compromise. Gonzales [ 25 ] address the pulmonary barrier, both endothelial as well as epithelial.…”
Section: Is Epithelial Barrier Compromise a Common Occurrence In Dise...mentioning
confidence: 99%
“…Mucin, the main component of saliva, can change in the pathological condition of the salivary gland. In addition, the over-expression of mucin is promoted by pro-inflammatory cytokines, and cytokine production is associated with an increase in ROS [58][59][60]. Huang et al reported that db/db mice demonstrated that PAS-positive mucins accumulated in the acini of submandibular glands [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the over-expression of mucin is promoted by pro-inflammatory cytokines, and cytokine production is associated with an increase in ROS [58][59][60]. Huang et al reported that db/db mice demonstrated that PAS-positive mucins accumulated in the acini of submandibular glands [58]. Mucin accumulation in salivary glands also suggests that the salivary secretory function was decreased under hyperglycemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…TJs are intercellular junctional complexes composed of more than 40 different proteins that regulate the transport of water, ions, and solutes through the paracellular pathway in epithelia and endothelia (Baker, 2016). Recently, several members of the claudin multigene family of TJ proteins have been described and some of them are shown to confer selective barrier properties on TJs, such as claudin‐1, claudin‐3, claudin‐4, and claudin‐5 (Huang et al., 2020; Min et al., 2020). Notably, claudin‐4 is mainly distributed and expressed in ductal cells in rodent salivary glands, which may affect the barrier properties of their TJs (Peppi & Ghabriel, 2004; Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%